THE APPLICATION OF STANDARDIZED HEALTH SERVICE FEES IN THE HEALTH INSURANCE SCHEME - Endartiwi, Sri Sularsih; Ispandiyah, Woro (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: The implementation of the Indonesian Minister of Health Regulations No. 3 of 2023 on the standard health service tariff in the national health insurance program, as a replacement for the previous policy, has created confusion among field implementers. The capitation rate is considered sufficient but is sometimes insufficient to cover Public Health Care (PHC) operational costs. Aims: This study aims to analyze standard health service tariffs in the implementation of the health insurance program at PHCs.  Methods: The authors used descriptive qualitative methods with a case study as the research design. The unit of analysis was the health service tariff standards at the PHCs. Data collection techniques involved snowball discussions followed by FGDs. Research subjects were selected using a purposive sampling technique. The FGDs consisted of 3 participants from BPJS Kesehatan, 4 from the public health centers, 2 people from private clinics, and 3 individual practitioner doctors. Data were analyzed using Open Code software. In addition, a policy analysis of PHC tariff standards was also conducted.  Results:  PHCs have implemented the Minister of Health Regulations No. 3 of 2023 since February 2023. In the implementation of health service tariff standards at the PHCs, no significant obstacles were encountered, as they adjusted to the applicable policies. Although the tariff standards follow Minister of Health Regulations No.3 of 2023 and include an increase in the capitation value compared to the previous policy, the amount is perceived as inadequate and still below the reasonable cost required for service delivery. Private clinics and individual practitioners must still cover operational expenses using capitation funds supplemented by income from non-insured patients to meet operational costs related to human resources, equipment, and supporting facilities. Conclusion: PHCs have implemented the standard health service tariff in accordance with the existing policy. However, the increase in capitation fees has not fully covered the costs at PHCs. Keywords: health service; PHC; tariff standard